Interpreting the History of Madihin Culture as Banjar Oral Literature and the Meaning Contained in Its Performances - Muhammad Rico; Muhammad Riduan; Rudy Prasetyo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Madihin is a form of Banjar oral literature. Madihin was originally an art intended for nobles or royal families. However, as time went by, this art became folk art. This article discusses the origins of madihin, the substance, function, instruments and values contained in madihin. The research method is library research, which is a type of research carried out by reading books or journals and other data sources to collect data from various literature both in libraries and other places, and bibliographic techniques which are carried out by reading, reviewing and taking notes on various important literature. The results of the research show that Madihin is a form of regional literature that was born, grew and developed in Banjar society. Madihin was born from the cultural combination of the Banjar people, which was initially still influenced by Hindu culture with Malay culture which had an Islamic culture. There are 2 values contained, namely holiness values and spirit or spiritual values. The meaning of Madihin oral literature performances has long been used as a medium of communication between the kingdom (king or palace officials) and its people. So it is very relevant if madihin is said to be one of the folk arts that is very communicative for the Banjar people.